2020
DOI: 10.3390/ijms21020677
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Regulates Bone Fracture Healing

Abstract: Bone fracture healing involves the combination of intramembranous and endochondral ossification. It is known that Indian hedgehog (Ihh) promotes chondrogenesis during fracture healing. Meanwhile, Sonic hedgehog (Shh), which is involved in ontogeny, has been reported to be involved in fracture healing, but the details had not been clarified. In this study, we demonstrated that Shh participated in fracture healing. Six-week-old Sprague–Dawley rats and Gli-CreERT2; tdTomato mice were used in this study. The right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Osterix (Osx) is an essential transcription factor for osteoblast differentiation; bone cannot form without it. Takebe et al was able to observe Osx-positive cells on the surface of a newly formed bone matrix seven days after the fracture [46]. We saw very few Osx-positive cells, particularly in the + Sr and non-scaffold groups.…”
Section: Bone and Tissue Regenerationmentioning
confidence: 45%
“…Osterix (Osx) is an essential transcription factor for osteoblast differentiation; bone cannot form without it. Takebe et al was able to observe Osx-positive cells on the surface of a newly formed bone matrix seven days after the fracture [46]. We saw very few Osx-positive cells, particularly in the + Sr and non-scaffold groups.…”
Section: Bone and Tissue Regenerationmentioning
confidence: 45%
“…Hedgehog signaling is involved in fracture healing. 167 In the early phase of fracture repair, the expression of SHH is detected in proliferating callus-forming cells in the periosteum. 168 SHH has an important role to facilitate both angiogenesis and osteogenesis in vivo and in vitro.…”
Section: Sonic Hedgehogmentioning
confidence: 99%
“…Shh gene delivery also inhibited radiation-induced cell senescence in the salivary glands of mice [115]. Some researchers found that compared with young mice (5 weeks old), the expression of Shh decreased in osteoblasts but increased in osteoclasts in old mice (60 weeks old), which is closely related to senile fracture healing [116], due to colocalization of Shh and Gli1 with osteogenic markers Runx2 and Osx, both of which can be observed during fracture healing [117]. Accumulated evidence indicated that resveratrol and two of its glycosides, polydatin and THSG, could activate the Shh pathway [75][76][77] and delay cell senescence [118][119][120][121][122].…”
Section: Notch/jaggedmentioning
confidence: 99%